2022
DOI: 10.1136/bmjopen-2021-059300
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence and correlates of perinatal depression in a case-cohort study of depression

Abstract: ObjectivesThis study sought to evaluate the prevalence, timing of onset and duration of symptoms of depression in the perinatal period (PND) in women with depression, according to whether they had a history of depression prior to their first perinatal period. We further sought to identify biopsychosocial correlates of perinatal symptoms in women with depression.Design and settingThe Australian Genetics of Depression Study is an online case cohort study of the aetiology of depression. For a range of variables, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Alanine, methionine, pyruvate, and glucose remained significant upon fully controlling for the effects of all six covariates prior to FDR adjustment. This finding indicates that these biomarkers may provide additional discriminatory information, and thus a closer relationship with prenatal depression and greater EPDS scores [ 64 , 65 ], not seen for the other metabolites which would benefit from further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Alanine, methionine, pyruvate, and glucose remained significant upon fully controlling for the effects of all six covariates prior to FDR adjustment. This finding indicates that these biomarkers may provide additional discriminatory information, and thus a closer relationship with prenatal depression and greater EPDS scores [ 64 , 65 ], not seen for the other metabolites which would benefit from further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Bahadur et al [86] noted that CEA increased the risk of PPD nearly seven-fold after adjusting for sociodemographic factors, whereas CPA and CSA were not significant. However, a larger Australian study [87] showed a similar but lower risk for CEA (aOR = 1.4). Nagl et al [88] found that women with severe CEA were nearly 20 times more likely to have PPD.…”
Section: Postpartum Depression (Ppd)mentioning
confidence: 89%
“…We reported that the risk elevation of suicidal behavior, although attenuated over time, remained elevated even 18 years later. Emerging data indicate that some PND could last for 7 years after delivery and may entail nonperinatal mental disorders . Such consequences may explain the risk of suicidal behavior later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data indicate that some PND could last for 7 years after delivery 52 and may entail nonperinatal mental disorders. 53 Such consequences may explain the risk of suicidal behavior later in life. Some risk factors (eg, low social support 54 ) may extend beyond the perinatal period and be associated with increased suicidal behavior in the long run.…”
Section: Discussionmentioning
confidence: 99%